Peculiarities of Immune Reactivity in Women with Urogenital Disorders in Perimenopause Period - Scherbina, I. N. (Problems of Cryobiology and Cryomedicine, 2008)
The peculiarities of immune reactivity in women with urogenital disorders within perimenopause period were studied. It has been established that in patients with urogenital disorders the impairments in immune system are tightly associated to the reduction of antimicrobal immunity and disturbances in the system of phagocyte cells.